Opportunities and Rationality Against Academic Cheating - Salsabilla, Yolanda; Uyun, Muhamad (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Although it is thought that the educational system will generate moral heirs to the country, the reality is that academic fraud is causing the nation's morale to crumble right now. scholastic fraud is an intentional act of dishonesty or fraud that is done in order to satisfy or finish scholastic requirements and/or duties. Opportunity and logic are two factors that contribute to academic dishonesty. Students commit academic fraud due to logic and abundant opportunities. The purpose of this study is to ascertain how opportunity and reason affect academic fraud. The study participants were current psychology faculty students. 191 participants were sampled via purposive random sampling. Data was gathered utilizing measuring instruments in the form of a Google Form, including opportunity scales, rationality scales, and academic fraud measures. employing multiple regression to analyze data. The examination of the data yields the significant value of p = 0.000 (0.000 0.005), which indicates that opportunity and rationality have an effect on academic cheating. The study's findings indicate that academic fraud occurs more frequently the more options and rationality pupils have.Sistem pendidikan dianggap akan melahirkan pewaris moral bagi negara, kenyataannya kecurangan akademik menyebabkan moral bangsa runtuh saat ini. penipuan skolastik adalah tindakan ketidakjujuran atau penipuan yang disengaja yang dilakukan untuk memenuhi atau menyelesaikan persyaratan dan / atau tugas skolastik. Peluang dan logika adalah dua faktor yang berkontribusi terhadap ketidakjujuran akademik. Mahasiswa melakukan kecurangan akademik karena logika dan kesempatan yang melimpah. Tujuan dari penelitian ini adalah untuk memastikan bagaimana peluang dan alasan mempengaruhi kecurangan akademik. Peserta penelitian adalah mahasiswa fakultas psikologi saat ini. 191 peserta diambil sampelnya melalui purposive random sampling. Pengumpulan data dilakukan dengan menggunakan alat ukur berupa Google Form, meliputi skala peluang, skala rasionalitas, dan ukuran kecurangan akademik. menggunakan regresi berganda untuk menganalisis data. Pengujian data menghasilkan nilai signifikan p = 0,000 (0,000 0,005), yang menunjukkan bahwa peluang dan rasionalitas berpengaruh terhadap kecurangan akademik. Temuan penelitian menunjukkan bahwa kecurangan akademik lebih sering terjadi, semakin banyak pilihan dan rasionalitas yang dimiliki siswa.